Force System Developed by Mushroom Archwires for Incisor Retraction: A Numerical Study - Do Amaral Ferreira, Marcelo; Mandello Rodrigues, Fabio Rodrigo; Luersen, Marco Antônio; Borges, Paulo César; Nanda, Ravindra; Rodrigues de Almeida, Márcio (Orthodontic Journal of Nepal, 2024)
Introduction: Mushroom archwires (MA) were developed to maintain incisor torque during retraction, i.e., control of root position via a generated couple while preserving posterior anchorage. This is achieved through a differential anchorage, either by translation or by controlled movement of the crown and root apex, in cases involving premolar extraction. Although their clinical application has been reported in the literature, the force system resulting from their activation has not yet been demonstrated. The aim of this study was to perform numerical simulations to analyze the force system generated by MA. Materials & Methods: A MA was geometrically modeled using Autodesk Inventor, and finite element analysis (FEA) was performed in ANSYS Workbench to simulate its mechanical behavior. For this simulation, non-linear analysis was used in order to take into account the large displacements effects, which consisted of pre-activation at their posterior extremities by 45° gable bends; restriction of the posterior extremities to mimic the insertion in the molar tubes and spacing between the vertical extremities (legs) 2.5 mm apart. Loops were activated at 4.0 mm and at 5.0 mm. Results: At 4.0 mm and 5.0 mm of activation, the archwire generated forces (Fx) of 184 gf and 251 gf, respectively. The corresponding Mz/Fx ratios were 12.9 mm and 10.6 mm, respectively. Conclusion: MA could be activated up to 5.0 mm for incisor retraction, which may be compatible with the biological limits of tooth movement during incisor retraction.